Migration and public finances in the EU - Carlo V. Fiorio; Tommaso Frattini; Andrea Riganti; Michael Christl (European Commission, Joint Research Centre (JRC), 2022)
We provide novel and comprehensive evidence on the net fiscal contributions of natives and migrants to the governmental budgets of EU countries. We account for income taxes and cash benefits, along with indirect taxes and in-kind benefits, which are often missing in standard datasets. We find that on average, migrants were net contributors to public finances over the period of 2014-2018 in the EU and, moreover, that they contribute approximately e1.5 thousand more per capita each year than natives. We also show that this difference is partly due to selection on characteristics that make migrants net fiscal contributors, such as demographic factors and employment probability.
Keywords: F22; H24; H50; 330; Migration; EU; individual taxation; public benefits; individual fiscal contribution